Games of Rapport - Corbin, Sandra J. (Canadian Journal of Counselling and Psychotherapy, 2012)
A series of board games called Games of Rapport arc currently being developed at the University of Alberta. The first in the series: "Angels and Devils" is designed for playby residents in a nursing home environment. Results of a study involving play of "Angels and Devils" by nursing home residents is interpreted as showing that board games can be useful in communicating rehabilitative objectives and in promoting discussion of sources of conflict in the nursing home social environment. A second game in the series: "Roles", initially developed for play in a delinquent counselling centre, is now being adapted forplay in nursing homes. Games of Rapport appear to have potential for facilitating communication in a variety of counselling and training contexts.